Pengujian Boiler untuk Pembangkit Listrik Tenaga Panas Laut - Andi Hendrawan; Leonardus Heru Pratomo; Sri Pramono; Lusiani Lusiani (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
Energy needs are one of the reasons why research on renewable energy is the choice. One of the renewable energies is OTEC (ocean thermal energy conversion) with sea surface heat being an energy source and boilers being a medium for converting heat energy into motion energy so that in the end it becomes electrical energy. Boilers are a vital part of a generator, so boiler testing is a requirement for a generator. The research was carried out by experiment by testing the boiler with various temperatures and pressures so as to produce output power. The results show that temperature and pressure are highly correlated with output power. The application of OTEC shows that temperature and pressure are things that must be considered, the higher the surface temperature, the greater the output power.